Numerical Study for Time Delay Multistrain Tuberculosis Model of Fractional Order - Nasser Hassan Sweilam; Seham Mahyoub Al-Mekhlafi; Taghreed Abdul Rahman Assiri (Complexity)
A novel mathematical fractional model of multistrain tuberculosis with time delay memory is presented. The proposed model is governed by a system of fractional delay differential equations, where the fractional derivative is defined in the sense of the Grünwald–Letinkov definition. Modified parameters are introduced to account for the fractional order. The stability of the equilibrium points is investigated for any time delay. Nonstandard finite deference method is proposed to solve the resulting system of fractional-order delay differential equations. Numerical simulations show that nonstandard finite difference method can be applied to solve such fractional delay differential equations simply and effectively.